The Psychometric Properties of a Portuguese Version of the Trait-Meta Mood Scale: an Attachment Framework - Cabral, Joana (2022)
This study examined the psychometric properties of the Portuguese version of Trait Meta-Mood Scale (TMMS). The TMMS is a self-report measure that assesses stable individual differences in the way people attend, discriminate, and repair their mood and emotions. Exploratory and confirmatory factor analyses (CFA) were conducted in a sample of 1070 Portuguese university students, aged 17–30 years. Attachment, coping and rumination measures were used to establish construct validity, and internal consistency was also tested. The CFA failed to gather support for the original three-factor structure. Results suggested that a four-factor structure, including 26 items tapping suppression, clarity, repair, and difficulties in defensive repression provided the best fit to the data. The four subscales evidenced good internal consistency. In addition, concurrent validity with attachment, coping, and rumination variables was determined. This four-factor structure provided a valid and reliable measure to assess emotion regulation and is proposed to add some comprehensive value to the assessment of emotion regulation under an information-processing and attachment framework.